Relations between grain yield and photosynthetic parts above the flag leaf node in barley - Yap, Thoo Chai; Harley, B. L. (Canadian Science Publishing, 1972)
All possible crosses, including reciprocals, among seven Hordeum vulgare l. cultivars of diverse origim were evaluated in the field in 1969 and 1970. The results of graphical and multiple regression analyses show that estimated areas of head surfase , penduncle surface, flag leaf area, and erectophile portion of the flag leaf were highly associated with grain yield. thus these above the flag leaf node might be good indicators of potential grain yield. The developmentalpatterns from anthesis to maturity for each of these traits were similar in the homozygotes and the heterozygotes. There were, however, substantials differences in magnitude for these traits between genotypes. Possible ways to establish a high yielding plant type are discussed.